Web-top robotics. - Hirukawa, H.
This paper deals with the use of the World Wide Web (WWW) as a platform for building robotic systems. We revisit the anatomy of the WWW system together with CORBA, the standard object request broker architecture, and show how to map robotic systems on it. We also review the current status of several meta-computing infrastructures for distributed computing on a wide-area network. Several implementation results are also shown
Keywords: CORBA; World Wide Web; Distributed computing; Meta-computing.; Object request broker architecture; Robotic system CAD; Web platform; Wide-area network